Effects of risk assessment and management programme for hypertension on clinical outcomes and cardiovascular disease risks after 12 months: a population-based matched cohort study. Issue 3 (March 2017) - Yu, Esther Y.T.; Wan, Eric Y.F.; Wong, Carlos K.H.; Chan, Anca K.C.; Chan, Karina H.Y.; Ho, Sin-yi; Kwok, Ruby L.P.; Lam, Cindy L.K.
Abstract : Objectives: This study evaluated the effectiveness of a structured multidisciplinary risk assessment and management programme for patients with hypertension (RAMP-HT) who were managed in public primary care clinics but had suboptimal blood pressure (BP) control in improving BP, LDL-cholesterol (LDL-C) and predicted 10-year cardiovascular disease (CVD) risk after 12 months of intervention. Methods: A total of 10 262 hypertension patients with suboptimal BP despite treatment, aged less than 80 years and without existing CVD were enrolled in RAMP-HT between October 2011 and March 2012 from public general out-patient clinics in Hong Kong. Their clinical outcomes and predicted 10-year CVD risk were compared with a matched cohort of hypertension patients who were receiving usual care in general out-patient clinics without any RAMP-HT intervention by propensity score matching. Multivariable linear and logistic regressions were used to determine the independent effectiveness of RAMP-HT after adjusting for potential confounding variables. Results: Compared with the usual care group after 12 months, significantly greater proportions of RAMP-HT participants achieved target BP (i.e. BP < 140/90 mmHg) (OR = 1.18, P  < 0.01) and LDL-C levels (i.e. <3.4 mmol/l for patients with CVD risk ⩽20% or <2.6 mmol/l for CVD risk >20%) (OR = 1.13, P  < 0.01). RAMP-HT participants also had significantly greater reduction in predicted 10-year CVD risk by 0.44% (coefficient = −0.44, P  < 0.01). Conclusion: The structured multidisciplinary RAMP-HT was more effective than usual care in achieving target BP, LDL-C and reducing predicted 10-year CVD risk in public primary care patients with suboptimal hypertension control after 12 months of intervention. A long-term follow-up should be conducted to confirm whether the improvement in clinical outcomes can be translated into actual reductions in CVD complications and mortalities and whether such approach is cost-effective.